Multiscale Synergistic Mechanism of Fiber-Reinforced Aerogel Composites Thermal Insulation and Flame Retardant Performance Optimization and Engineering Applications - Mishra, Subhamoy; Ratke, Jessica (Journal of Functional Materials and Applied Engineering, 2024)
Fiber-reinforced aerogel composites are gaining traction for ultra-high-temperature service because they marry super-insulation with minimal weight and robust dimensional integrity. Here we critically survey synthesis routes, pore-scale architecting tactics, and the cooperative physics that suppresses heat and fire simultaneously. Tailoring both the fiber family and the fiber–matrix boundary chemistry delivers simultaneous gains in mechanical strength and upper-use temperature. By optimizing drying processes, the pore structure was tailored, achieving thermal conductivity as low as 0.018–0.065 W/(m·K). The multiscale structure—nanopores limiting gas conduction, micro-fibers providing skeleton support, and infrared opacifiers reducing radiative heat transfer—along with organic-inorganic hybrid precursors, collectively contributed to superior high-temperature performance. These materials exhibit broad application potential in aerospace thermal protection, building energy efficiency, and power battery thermal management. Future research should focus on multiscale simulation, smart functional coatings, and green manufacturing processes to facilitate industrial applications.